The Holmberg Collection of Skin Clothing from Kodiak Island at the National Museum of Denmark - Schmidt, Anne (Études Inuit Studies, 2018)
In 1851, during his stay in what was then Russian America, Finnish scientist Henrik Johan Holmberg (1818–1864) collected a unique assortment of some four hundred objects primarily from the Indigenous people of southern Alaska and the Northwest Coast. The collection included skin clothing, dress ornaments, hunting equipment, household tools, and ceremonial objects from the Koniags (of Kodiak Island off the coast of South Alaska) and the Tlingit (along the Pacific Northwest Coast). On his journey home in 1852, Holmberg visited Copenhagen and the Museum of Northern Antiquities (later the National Museum of Denmark). There, he met Christian Jürgensen Thomsen (1788–1865), museum director, Danish antiquarian, and creator of the so-called “three-period system,” which divided early human history into the Stone Age, Bronze Age, and Iron Age. Last, but not least, Thomsen founded the first ethnographic museum in the world. Thomsen, who never missed an opportunity to increase the museum’s collections, succeeded in buying Holmberg’s collection from him, perhaps because of Holmberg’s poor finances. The Holmberg Collection consists of unique specimens from a period before the Indigenous population was forever influenced by the cultural changes that were introduced with the early Russian trade. This article focuses the Holmberg Collection of skin clothing, which differed considerably from that of the more northerly Inuit people. The collection is part of the Danish National Museum’s interdisciplinary research initiative Northern Worlds, under the subproject “Skin Clothing from the North,” which includes the museum’s large collection of skin clothing from circumpolar Indigenous people.